Exploring the invasion of the guttural toad Sclerophrys gutturalis in Cape Town through a multidisciplinary approach - Vimercati, Giovanni (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.